The Constitution in Congress descent into the maelstrom, 1829-1861 - Currie, David P. (Chicago, Ill. : University of Chicago Press, 2005)
This biography of the US constitution offers a survey of the congressional history behind its development. David Currie looks at the debate over slavery and how this divisive issue led the country into civil war, focusing on the period from the Jacksonian revolution of 1829 to the secession of the Southern States.
Specialized.
Description based on print version record.
Includes index.
Keywords: United States. -- Congress -- History; Constitutional history -- United States; Law -- United States -- History; Legislative power -- United States -- History; Executive power -- United States -- History; United States -- Politics and government -- 1815-1861.; Law; United States of America, USA; 19th century, c 1800 to c 1899.; Politics & government; Constitution: government & the state; Jurisprudence & general issues